Challenges in the Design and Implementation of an English Placement Test for a Colombian Public University - Ramirez, Alexander (GIST – Education and Learning Research Journal, 2020)
This reflection paper disseminates the design and implementation of an English placement test for first semester students from different majors. This design was carried out within the framework of a research project in a Colombian public university. The article seeks to scrutinize the stages leading to a test, so that language teachers who embark for the first time on the task of designing placement exams have a model and can anticipate the various vicissitudes of academic and administrative nature that may arise. The conclusions derived from the process of construction and implementation of the test highlight the lack of training and literacy in the area of ​​language testing, as well as the existing tensions between academic expectations and the administration within a university institution.